Target-Controlled Infusion (TCI) Propofol in Ventriculoperitoneal (VP) Shunt Surgery during the First Trimester of Pregnancy - Albinus Yunus Cobis; Dewi Yulianti Bisri; Iwan Abdul Rachman (Perhimpunan Dokter Spesialis Anestesiologi dan Terapi Intensif, 2021)
Background: The use of target-controlled infusion (TCI) propofol in pregnant patients undergoing ventriculoperitoneal (VP) shunt surgery during the first trimester due to hydrocephalus presents a rare and complex challenge in neuroanesthesia. TCI propofol is favoured for its ability to maintain hemodynamic stability and effectively control intracranial pressure (ICP), both of which are crucial in neuro-obstetric management.Case: A 23-year-old woman, five weeks pregnant, with a history of communicating hydrocephalus and bilateral VP shunts, presented with severe headache. She underwent emergency VP shunt revision under general anesthesia using TCI propofol (Schnider model, target effect-site concentration 2.5–5 mcg/mL), fentanyl (2 mcg/kg), atracurium (0.5 mg/kg), and lidocaine (1.5 mg/kg). Intraoperative hemodynamics remained stable throughout the two-hour procedure. Postoperatively, her neurological status improved significantly, and no complications were observed.Discussion: Compared to inhalational agents such as sevoflurane, TCI propofol demonstrates superior control of ICP, maintains cerebral blood flow stability, and facilitates faster postoperative recovery. Fentanyl, atracurium, and lidocaine were selected due to their favourable safety profiles for short-term use in pregnancy. Postoperatively, progesterone was administered to support pregnancy maintenance by reducing uterine contractility and mitigating the risk of miscarriage associated with surgical and anesthetic stress.Conclusion: TCI propofol is an effective and safe anesthetic strategy for managing VP shunt procedures during the first trimester of pregnancy. A multidisciplinary approach is essential to achieve optimal neurological and obstetric outcomes.